Perbandingan Kualitas Minyak Pirolisis, Minyak Tanah, dan Solar - Shafwan Amrullah; Rena Jayana; Ghina Fadhilah; Anggita Dwi Puspita (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2021)
Plastic is a polymer compound whose main constituent elements consist of carbon and hydrogen where one of the raw materials that is often used to make plastic is naphtha, which is a material produced from refining petroleum or natural gas (Surono, 2013). Chemical decomposition through a heating process without oxygen where the raw material will undergo a breakdown of the gas phase structure called pyrolysis (Jahiding et al., 2020). The quality comparison of pyrolisis oil, kerosene and oil, namely pyrolysis oil is lower than the quality of kerosene but higher than diesel oil based on density oil, duration of combustion, water temperature and volume of water that evaporates. Based on the research that has been done by Wahyudi (2018) and Mustam (2021) which is shown from the comparison chart of kerosene, pyrolysis oil and diesel oil based on the density of oil, duration of oil burning, temperature of cooked water and vaporized water volume. The quality of kerosene is better when compared to pyrolysis oil and diesel oil which is determined by the flash point of kerosene which is lower between pyrolysis oil and diesel oil, which is 47.8 oC. The flash point of diesel oil is 55 oC (the data on the flash point of kerosene and diesel oil were obtained from the Ministry of Energy and Mineral Resources in 2006). While the point of pyrolysis oil can be under the range of more than 47.8 oC and less than 55 oC. This is because the quality of pyrolysis oil is between kerosene and diesel oil.